PENDUGAAN UMUR SIMPAN GARAM FORTIFIKASI KELOR MENGGUNAKAN METODE ASLT - Resty Putri Ariesta Shandy; Iffan Maflahah; Asfan Asfan (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
Moringa fortification salt is a salt that has the addition of nutrients using Moringa extract as an additional ingredient. Research objectives: 1) determine the effect of storage temperature and type of packaging on the quality of Moringa fortification salt. 2) determine the shelf life of the Moringa fortified salt product by estimating the shelf life of the Accelerated Shelf Life Testing (ASLT) method. The method used is the Arrhenius Model Accelerated Shelf Life Testing (ASLT). The results showed that differences in storage temperature and type of packaging significantly affected the color parameters of organoleptic tests, vitamin A, and vitamin C. The type of packaging significantly affected the parameters of NaCl content and color test (b). Shelf life of Moringa fortification salt using PET plastic bottle packaging temperature 60°C 16,71 months PET plastic bottle packaging temperature 45°C 15,86 months aluminum foil packaging temperature 60°C 15,17 months aluminum foil packaging temperature 45°C C 14,80 months PET plastic bottle packaging temperature 30°C 14,30 months aluminum foil packaging temperature 30°C 13,47 months.